Effect of word card media on grade 1 students’ early reading skills - Mardiah, Dede; Cahyani, Isah; Putri, Yasmin Gehan; Ulfiyani; Mayang, Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Language skills are essential in daily life, particularly in education. At the elementary level, reading development progresses through basic and advanced stages. Many first-grade students continue to struggle with early reading due to inadequate learning stimulation, limited use of instructional media, and low engagement during lessons. This study investigates the effect of using word card media on the early reading skills of first-grade students at SDN Purwadadi 1, Subang Regency. A pre-experimental method with a one-group pretest-posttest design was applied, involving 27 students. Data were collected through a performance assessment test, where students demonstrated their reading abilities before and after the intervention. The results showed an improvement in the average score from 58.96 in the pretest to 65.11 in the posttest, with a 10.43% increase. Statistical analysis using the Wilcoxon Signed Rank Test showed a significance value of < 0.05, indicating a meaningful difference between the two tests. The findings suggest that word card media effectively enhances early reading skills, creates a more engaging learning experience, and increases student participation in the classroom. It is recommended that teachers integrate word card media into early reading instruction to enhance student interest, increase engagement, and improve reading outcomes.